Pengaruh Integrasi Media Komunikasi Terhadap Pengetahuan Pengunjung Wisata Edukasi Pertanian Kabupaten Tulungagung - Mochlisin Fatkur Rohman; Gunawan Gunawan; Ugik Romadi (Jurnal Penyuluhan, 2022)
Indonesia has a lot of natural wealth that can be used as a ecotourism or tourism village. One of the tourism village developments is in Bono Village, Boyolangu Sub district, Tulungagung Regency. The tourism is Agricultural Education Tourism Belimbing Artha Mandiri Farmer Group. Agricultural education tourism is very potentially visited by tourists because of the quality of products and knowledge given to visitors. Agricultural education tourism managers must raise agricultural education in their tourism, because educational tourism aims to educate visitors about agricultural sciences, so the renewal communication media is necessary to support the achievement of these goals. The purpose this study is to describe the characteristics visitors and analyze the influence of visitor characteristics and the integration of communication media on the knowledge of visitors. The research method used is Descriptive Quantitative. Determination respondents' samples using proportionate stratified random sampling techniques, as well as data analysis used is multiple linear regression. The results of this study showed the level knowledge of visitors is at the stage of understanding and the presence a significant influence between the variable characteristics of visitors and the integration of communication media to the level knowledge of visitors.